Leap Motion Device Used to Control a Real Anthropomorphic Gripper. (6th June 2016) - Staretu, Ionel; Moldovan, Catalin
This paper presents for the first time the use of the Leap Motion device to control an anthropomorphic gripper with five fingers. First, a description of the Leap Motion device is presented, highlighting its main functional characteristics, followed by testing of its use for capturing the movements of a human hand's fingers in different configurations. Next, the HandCommander soft module and the Interface Controller application are described. The HandCommander is a software module created to facilitate interaction between a human hand and the GraspIT virtual environment, and the Interface Controller application is required to send motion data to the virtual environment and to test the communication protocol. For the test, a prototype of an anthropomorphic gripper with five fingers was made, including a proper hardware system of command and control, which is briefly presented in this paper. Following the creation of the prototype, the command system performance test was conducted under real conditions, evaluating the recognition efficiency of the objects to be gripped and the efficiency of the command and control strategies for the gripping process. The gripping test is exemplified by the gripping of an object, such as a screw spanner. It was found that the command system, both in terms of capturing human hand gestures with the Leap Motion device and effective object gripping, is operational. Suggestive figures are presented as examples.